2009
DOI: 10.1017/s1751731109990255
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HMGR and corresponding cholesterol content in tissues of two pig breeds

Abstract: The 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) is an essential enzyme in cholesterol biosynthesis. To study the expression of HMGR and corresponding cholesterol content in liver, adipose and muscle, six Chinese local breed (Huai pig) and Landrace pigs were selected. The results indicated that significant differences of cholesterol content in adipose ( P , 0.01), liver ( P , 0.05) and muscle ( P , 0.01) tissues were detected between pigs of differing genetic backgrounds. HMGR mRNA expression were noted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…There is a 107-fold difference between these two tissues (data not shown), suggesting that HMGR gene plays an important role in the liver. HMGR is the rate-limiting enzyme in cholesterol synthesis, we therefore speculated that the liver was likely to be a major site of cholesterol synthesis, which was consistent with the results of Romos et al (Romos et al, 1971)and with the reports in Huai and Landrace pigs (Liu et al, 2009), human and chicken (Sato et al, 2003). In addition, the high levels of expression in heart, kidney, bladder, and subcutaneous fat indicates that HMGR gene also plays important roles in those tissues.…”
Section: Discussionsupporting
confidence: 90%
“…There is a 107-fold difference between these two tissues (data not shown), suggesting that HMGR gene plays an important role in the liver. HMGR is the rate-limiting enzyme in cholesterol synthesis, we therefore speculated that the liver was likely to be a major site of cholesterol synthesis, which was consistent with the results of Romos et al (Romos et al, 1971)and with the reports in Huai and Landrace pigs (Liu et al, 2009), human and chicken (Sato et al, 2003). In addition, the high levels of expression in heart, kidney, bladder, and subcutaneous fat indicates that HMGR gene also plays important roles in those tissues.…”
Section: Discussionsupporting
confidence: 90%
“…Cholesterol biosynthesis de novo, is largely controlled by a crucial rate limiting enzyme HMGR. This enzyme is controlled by four distinct mechanisms: feed-back inhibition, control of gene expression, rate of enzyme degradation and phosphorylationdephosphorylation (DeBose-Boyd, 2008;Liu et al, 2009). The present study measured the mRNA expression of HMGR and related genes including PPP2CA, PPP2CB, PPP3CA, PRKAA1, PRKAA2, and STK11, and found that dietary LAB dose above 3 × 10 7 cfu/kg significantly downregulated the expression of these genes in the liver.…”
Section: Discussionmentioning
confidence: 59%
“…However, other authors have reported discrepant results. The representative of lean breeds, Landrace, had less cholesterol compared to Mangalitsa pigs [ 55 ] and Chinese Huai pigs [ 56 ]. Large White also showed a lower content of cholesterol than Zlotnicka spotted, Pulawska and Mangalitsa pigs [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Large White also showed a lower content of cholesterol than Zlotnicka spotted, Pulawska and Mangalitsa pigs [ 10 ]. Although cholesterol can be derived from dietary sources and synthesised by the liver, different cholesterol biosyntheses can also be expressed by the pig genotype [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation